The stability of the financial system as a condition of ensuring the economic security of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
Questions of national security are crucial for any state. In the Republic of Kazakhstan in the conditions of an impending crisis government programs, strategic development plans related to the provision of stable development of the Kazakh society are adopted. It is well known, the national security is divided into different types. One of these is economic security.Under the conditions of forming a market economy, the problem of safe existence of the entire economic system of the country has become one of the most pressing. The Strategic Development Plan of the Republic of Kazakhstan until 2020 focuses on the need of implementing the measures directed to improving of the stability of the national economy to the negative effects of the global or regional crises through strengthening of the country’s financial system.Key words: Financial system, national security, economic security, stability, crisis, national interests.